Efektivitas Pelaksanaan Pelayanan Pengaduan Masyarakat Berbasis E-Government - Mahendra, Gerry Katon; Pribadi, Ulung (Universitas Muhammadiyah Yogyakarta, 2014)
Public complaints service today’s has become part of the efforts to improve public services in Indonesia. Government,both central and local levels is appropriate to give special attention to the improvement of service quality of publiccomplaints. The government’s attention can be achieved either by continuously innovate to create public complaintsservice that is not only easily accessible by the public, but also can be received and responded to effectively by localgovernment. Yogyakarta City’s Government innovates by providing the services of public complaints were based oninformation technology and communication (e-government). Innovations made by the government of Yogyakar ta isexpected to provide ease of access for the public and can be input which should be followed up effectively by thegovernment of the city of Yogyakarta so as to create improved quality of public services in general in the future.